Quantitative assessment of energy and resource recovery in wastewater treatment plants based on plant-wide simulations. (1st July 2017) - Fernández-Arévalo, T.; Lizarralde, I.; Fdz-Polanco, F.; Pérez-Elvira, S.I.; Garrido, J.M.; Puig, S.; Poch, M.; Grau, P.; Ayesa, E.
Abstract: The growing development of technologies and processes for resource treatment and recovery is offering endless possibilities for creating new plant-wide configurations or modifying existing ones. However, the configurations' complexity, the interrelation between technologies and the influent characteristics turn decision-making into a complex or unobvious process. In this frame, the Plant-Wide Modelling (PWM) library presented in this paper allows a thorough, comprehensive and refined analysis of different plant configurations that are basic aspects in decision-making from an energy and resource recovery perspective. In order to demonstrate the potential of the library and the need to run simulation analyses, this paper carries out a comparative analysis of WWTPs, from a techno-economic point of view. The selected layouts were (1) a conventional WWTP based on a modified version of the Benchmark Simulation Model No. 2, (2) an upgraded or retrofitted WWTP, and (3) a new Wastewater Resource Recovery Facilities (WRRF) concept denominated as C/N/P decoupling WWTP. The study was based on a preliminary analysis of the organic matter and nutrient energy use and recovery options, a comprehensive mass and energy flux distribution analysis in each configuration in order to compare and identify areas for improvement, and a cost analysis of each plant for different influent COD/TN/TP ratios. Analysing the plants from a standpoint of resources and energy utilization, a low utilization of the energy content of the components could be observed in all configurations. In the conventional plant, the COD used to produce biogas was around 29%, the upgraded plant was around 36%, and 34% in the C/N/P decoupling WWTP. With regard to the self-sufficiency of plants, achieving self-sufficiency was not possible in the conventional plant, in the upgraded plant it depended on the influent C/N ratio, and in the C/N/P decoupling WWTP layout self-sufficiency was feasible for almost all influents, especially at high COD concentrations. The plant layouts proposed in this paper are just a sample of the possibilities offered by current technologies. Even so, the library presented here is generic and can be used to construct any other plant layout, provided that a model is available. Graphical abstract: Highlights: Comparative analysis of evolutionary WWTP, from a techno-economic point of view. Analysis of organic matter and nutrient energy use and recovery options. Comparative analysis of COD and nutrient flux distributions in evolutionary plants. Analysis of the costs distributions in WWTPs for different influent COD/N/P ratios. Simulations based on the Plant-wide modelling methodology.